Penggunaan Pengungkit dalam Mengembangkan Bisnis - Idris Gautama (Bina Nusantara University, 2003)
Many businesses do not perform optimally because of the leveraging factors. This article explains the term leveraging, its factors, how it works, and also how the factors can influence the business. Starting with the concept of leverage then how its works followed by the importance of control activities in good corporate governance in order to put leveraging into maximum performance.